PENGARUH KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP LOYALITAS PELANGGAN PT. JNE DI KOTA BANDUNG - Arsyka, Farindria; Sasmita, Asep Hadian; Pratama, Pebi Yuda (Journal Industrial Engineering and Management (JUST-ME), 2025)
The increasing volume of products and high interest from users of logistics services require logistics services to be able to keep up with the situation. This study explores the effect of service quality and trust on customer loyalty at PT. JNE in Bandung City. Using a quantitative approach and involving 32 purposively selected respondents, this study applies multiple linear regression and partial T-test for data analysis. Individually, service quality and trust do not have a significant effect on customer loyalty. For service quality, the t-value is 0.808 (p = 0.426), and for trust, the t-value is 0.485 (p = 0.632). These findings indicate that, when viewed separately, service quality and trust may not be significant factors in influencing customer loyalty at PT. JNE Bandung City. Further research is recommended to explore other factors or expand the scope of the study in order to gain a more comprehensive understanding of the dynamics of customer loyalty in the context of courier services.